Strategi Geopolotik dalam Kebijakan Luar Negeri Suatu Negara - Sugiharto Sugiharto; Mulhady Putra; Amanda Anggraini; Aisyah Dwi Ramadhani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Geopolitical strategies are used in foreign policy in a country's efforts to overcome global challenges and maintain its national interests. This study investigates classical geopolitical theories such as Heartland and Rimland, as well as modern strategies such as realism, liberalism, and constructivism. The study focuses on how countries make their geopolitical plans, internal and external factors that influence foreign policy, and the close relationship between geopolitical strategies and state interests in terms of security, economy, politics, and social. The results of the study show that appropriate and flexible geopolitical strategies can strengthen a country's position on the international stage and play an important role in maintaining the stability and prosperity of the country. It is hoped that this study will help us understand the dynamics of geopolitics and a good way to make international policies.